Development of interactive media sheet metal design modeling based on software Autodesk Inventor Professional 2023 - Adi Pangestu, Deni Kusuma; Widiyanti, Widiyanti; Puspitasari, Poppy; Suyetno, Agus (Universitas Negeri Yogyakarta, 2024)
This research and development aims to produce learning media products presented interactively and practically based on Autodesk Inventor Professional 2023 student version software and analyze the feasibility level of learning media for CAD Manufacturing Drawing Techniques subjects to improve competence in the field of machining techniques at Vocational High School 1 Kediri. The type of research used is research and development (R&D) using the Borg and Gall model, It involved 6 students for the small-scale testing and 32 students for the large-scale testing. Based on the data obtained and descriptive analysis, among others, the results of media expert validation were 98.44%, material expert validation was 89.28%, small-scale trials were 92.08%, and operational trial results were 91.09%. These results indicate that the interactive learning media product sheet metal design modeling meets the criteria very well and can be utilized as a learning tool.